Pengaruh Kompensasi, Motivasi Intrinsik, dan Lingkungan Kerja terhadap Semangat Kerja Karyawan PT Ruang Raya Indonesia (Ruangguru) Jakarta Selatan - Nur Zalika, Naza; Septyarini, Epsilandri; Lysander, Mohammad Ahyar Syafwan (Efektor, 2024)
This research is based on the decreased morale experienced by PT Ruang Raya Indonesia (Ruangguru) employees in South Jakarta. This study aimed to determine the effect of compensation, intrinsic motivation, and work environment on employee morale. The research method used is a non-experimental descriptive quantitative method. Data was collected through questionnaires distributed to 60 employees of Ruangguru. Sampling technique, using a saturated sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that compensation and intrinsic motivation positively and significantly influence employee morale. The work environment is no less important, and the results indicate that the work environment has a positive and significant influence on employee morale. Overall, this study found that compensation, intrinsic motivation, and work environment together positively and significantly influence employee morale. The findings suggest that Ruangguru's management should pay attention to all three factors to improve employee morale, which can improve the company's overall performance.